Prolonged mechanical ventilation worsens sepsis-induced diaphragmatic dysfunction in the rat. - Matthieu Le Dinh; Serge Carreira; Julie Obert; Ghislaine Gayan-Ramirez; Bruno Riou; Maud Beuvin; Thomas Similowski; Catherine Coirault; Alexandre Demoule (PLoS ONE)
Background Short-term mechanical ventilation (MV) protects against sepsis-induced diaphragmatic dysfunction. Prolonged MV induces diaphragmatic dysfunction in non-septic animals, but few reports describe the effects of prolonged MV in sepsis. We hypothesized that prolonged MV is not protective but worsens the diaphragmatic dysfunction induced by a mild sepsis, because MV and sepsis share key signaling mechanisms, such as cytokine upregulation. Method We studied the impact of prolonged MV (12 h) in four groups (n = 8) of male Wistar rats: 1) endotoxemia induced by intraperitoneal injection of Escherichia coli lipopolysaccharide, 2) MV without endotoxemia, 3) combination of endotoxemia and MV and 4) sham control. Diaphragm mechanical performance, pro-inflammatory cytokine concentrations (Tumor Necrosis Factor-α, Interleukin-1β, Interleukin-6) in plasma were measured. Results Prolonged MV and sepsis independtly reduced maximum diaphragm force (-27%, P = 0.003; -37%, P<0.001; respectively). MV and sepsis acted additively to further decrease diaphragm force (-62%, P<0.001). Similar results were observed for diaphragm kinetics (maximum lengthening velocity -47%, P<0.001). Sepsis and MV reduced diaphragm cross sectional area of type I and IIx fibers, which was further increased by the combination of sepsis and MV (all P<0.05). Sepsis and MV were individually associated with the presence of a robust perimysial inflammatory infiltrate, which was more marked when sepsis and MV were both present (all P<0.05). Sepsis and, to a lesser extent, MV increased proinflammatory cytokine production in plasma and diaphragm (all P<0.05); proinflammatory cytokine expression in plasma was increased further by the combination of sepsis and MV (all P<0.05). Maximum diaphragm force correlated negatively with plasma and diaphragmatic cytokine production (all p<0.05). Conclusions Prolonged (12 h) MV exacerbated sepsis-induced decrease in diaphragm performance. Systemic and diaphragmatic overproduction of pro-inflammatory cytokines may contribute to diaphragm weakness.